2013
DOI: 10.1098/rspb.2013.0720
|View full text |Cite
|
Sign up to set email alerts
|

Social learning of predators in the dark: understanding the role of visual, chemical and mechanical information

Abstract: The ability of prey to observe and learn to recognize potential predators from the behaviour of nearby individuals can dramatically increase survival and, not surprisingly, is widespread across animal taxa. A range of sensory modalities are available for this learning, with visual and chemical cues being well-established modes of transmission in aquatic systems. The use of other sensory cues in mediating social learning in fishes, including mechano-sensory cues, remains unexplored. Here, we examine the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 50 publications
1
21
0
1
Order By: Relevance
“…Iowa darters (Etheostoma exile (Girard, 1859)) reduce exploratory behaviour and alter movement patterns in response to disturbance cues (Wisenden et al 1995). Likewise, orange clownfish (Amphiprion percula (Lacépède, 1802)) show a significant antipredator response to disturbance cues (Manassa et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Iowa darters (Etheostoma exile (Girard, 1859)) reduce exploratory behaviour and alter movement patterns in response to disturbance cues (Wisenden et al 1995). Likewise, orange clownfish (Amphiprion percula (Lacépède, 1802)) show a significant antipredator response to disturbance cues (Manassa et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…5962]. Learning about predators can occur through direct experience or through social learning from experienced individuals.…”
Section: Discussionmentioning
confidence: 99%
“…McCormick (2009) found that juvenile P. amboinensis were located further away from bleached and degraded coral than live coral and suggested that this may be due to the noxious cues from degrading habitat pushing individuals further away from the shelter. Olfactory cues are a crucial source of information with which to inform their activities, particularly for site-attached organisms, providing information on foraging opportunities (DeBose & Paul, 2014), available mates (Oliveira & Gonc ßalves, 2008), stressful encounters (Manassa et al, 2013) and successful or attempted predation events (L€ onnstedt & McCormick, 2015). By moving further away from degraded habitats, fish may be attempting to extract themselves from the boundary layer of the coral and enable themselves to receive unmodified olfactory information.…”
Section: Discussionmentioning
confidence: 99%